Isolation, Structural Analyses and Biological Activity Assays against Chronic Lymphocytic Leukemia of Two Novel Cytochalasins — Sclerotionigrin A and B - Petersen, Lene M. (Molecules, 2014)
Two new cytochalasins, sclerotionigrin A (1) and B (2) were isolated together with the known proxiphomin (3) from the filamentous fungus Aspergillus sclerotioniger. The structures and relative stereochemistry of 1 and 2 were determined based on comparison with 3, and from extensive 1D and 2D NMR spectroscopic analysis, supported by high resolution mass spectrometry (HRMS). Compounds 2 and 3 displayed cytotoxic activity towards chronic lymphocytic leukemia cells in vitro, with 3 being the most active.